Cost benefit analysis for Grevillea robusta in Ethiopia: linking establishment of a breeding seedling orchard to the economic returns of quality plantings - Pedercini, F.; Dawson, Ian K.; Lillesø, Jens-Peter B.; Moestrup, S.; Nørgaard, C.T.; Abiyu, A.; Eshete, G.; Jamnadass, Ramni; Graudal, L. (CIFOR-ICRAF, 2022)
This study was developed in the context of the Provision of Adequate Tree Seed Portfolios (PATSPO) initiative in Ethiopia. PATSPO aims to strengthen the existing tree-seed system by ensuring access to high-quality tree germplasm. Here, we estimate the socioeconomic impact of establishing a breeding seedling orchard (BSO) and distributing quality planting material of the tree Grevillea robusta (grevillea) in Ethiopia. Grevillea is a commercially important and popular agroforestry tree species grown in East African smallholder farms. Our study starts by modelling tree growth with a one-parameter regression fitted to literature-sourced growth characteristics. For the purpose of modelling, we identify three ‘quality scenarios’ (related to the germplasm used) and two ‘planting options’. Based on the model’s outputs, we investigate the effects of increased tree productivity on farmland economy, on the provision of environmental services, and on the wider forestry sector. Findings are outscaled based on the demand for grevillea planting material in Ethiopia and an assumed reach of PATSPO-derived high-quality germplasm. Our growth models indicated that higher than baseline quality scenarios could produce a significant increase in volume (and biomass productivity). This resulted in several-fold increases in the net present value over the production cycle of agroforestry and woodlot plantings, as well as significant benefits in other economic indicators. At the country scale, our analysis estimated that after 50 years the increase in cumulative net present value of on-farm grevillea plantings should be between Birr 2.7 billion and 1.9 billion when using high-quality germplasm compared to an unimproved germplasm baseline, a significant boost (38 Birr = 1 USD at the time of calculations in 2021). We therefore reveal that establishing a grevillea BSO in Ethiopia could produce significant economic returns for tree growers that are much higher than the initial investment that we determine to be required. Furthermore, using BSO germplasm compared to an unimproved germplasm baseline could over 50 years after the BSO’s establishment sequester an extra 1.7 million tonnes of CO2 equivalents annually and achieve an increase in net present value annually of Birr 44 million in roundwood milling into sawnwood. In summary, our current analysis indicated that a focus on grevillea’s germplasm quality is predicted to bring significant economic and environmental benefits in Ethiopia. Our approach to estimate the benefits of using quality germplasm in tree planting represents an advance on previous methods and can be widely applied to a broad range of species, production systems and locations.